An Evaluation of Women and the Ideological Interest of the Integrated Islamic School - Shalihin, Nurus; Amri , Mufti Ulil (JURNAL PENELITIAN, 2022)
This study explores the strategic use of female teachers as ideological agents in Integrated Islamic Schools (IIS) within Early Childhood Education (ECE) institutions in Padang, Indonesia. It examines how gender roles are utilized to transmit ideological values to young students, raising concerns regarding ideological exploitation. The study is framed within the broader discourse of religious radicalism and gender instrumentalization in education, drawing upon the structuralist paradigm to assess institutional dynamics. A qualitative approach was employed, with data collected through questionnaires distributed to 43 female teachers across 11 IIS-ECE institutions and complemented by in-depth interviews with school leadership. The findings reveal that IIS intentionally recruits female teachers based on specific ideological criteria and integrates them into religious programs post-recruitment. Women are positioned as culturally acceptable figures to convey Islamic ideological values due to prevailing gender stereotypes and societal norms. This process, although appearing empowering, in fact conceals a mechanism of ideological exploitation that reproduces conservative religious identities in early education. The study concludes that women in IIS are simultaneously positioned as victims and agents within a structured ideological system, which has significant implications for understanding gender, power, and ideology in Islamic schooling. Future research is encouraged to adopt alternative paradigms that center women’s agency and rationality in such educational settings.